AWARENESS AND VOLUNTARY CHARACTER AS THE FEATURES OF A DEED IN THE OBJECTIVE PART OF CORPUS DELICTI - T. Nagaeva (Russian Journal of Economics and Law)
The article investigates the issues of links between the objective and subjective parts of corpus delicti. Basing on the critical analysis of the specialists' opinions on the issue, the author comes to the conclusion about the criminal's behavioral act.